2020
DOI: 10.3389/fmolb.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Non-translational Connections of eEF1B in the Cytoplasm and Nucleus of Cancer Cells

Abstract: The human translation machinery includes three types of supramolecular complexes involved in elongation of the polypeptide chain: the ribosome, complex of elongation factors eEF1B and multienzyme aminoacyl-tRNA synthetase complex. Of the above, eEF1B is the least investigated assembly. Recently, a number of studies provided some insights into the structure of different eEF1B subunits and changes in their expression in cancer and other diseases. There is increasing agreement that possible disease-related functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…WT*, 36*, 55*,79*, FM*same as before but the samples were taken after pull down procedure. eEF1A binding to other subunits of the eEF1B complex [34]. Thus, in the case of eEF1Bγ, we actually observed the interaction of eEF1A2 with the eEF1B complex.…”
Section: Resultssupporting
confidence: 53%
“…WT*, 36*, 55*,79*, FM*same as before but the samples were taken after pull down procedure. eEF1A binding to other subunits of the eEF1B complex [34]. Thus, in the case of eEF1Bγ, we actually observed the interaction of eEF1A2 with the eEF1B complex.…”
Section: Resultssupporting
confidence: 53%
“…eEF1B has also been found in the nuclei of human cells. The interactome of nuclear eEF1Bβ indicates a putative role in transcription, splicing, and DNA damage response, whereas the interactome of nuclear eEF1Bγ suggests a role in the splicing and control of mRNA stability [236]. Moreover, eEF1Bγ binds the Rpb3 subunit of RNAP II and is recruited to the promoters of genes encoding vimentin, Che1 (AATF), and p53 in human cells [237,238].…”
Section: Roles Of Ctas In Transcriptional Regulationmentioning
confidence: 99%
“…It has been reported that the subunits involved into eEF1B can interact with several protein partners in human cancer cells (56). However, only translationally controlled tumor protein (TCTP) was shown to bind the CAR domain of eEF1B␤ (57) that resulted in inhibition of its guaninenucleotide exchange activity (58).…”
Section: Discussionmentioning
confidence: 99%